Avaliação da influência da infraestrutura de tecnologia da informação no impacto do compartilhamento do conhecimento na capacidade inovativa de empresas industriais - Cassia, Adalberto Ramos (2019)
This research aims to analyze the influence exerted by knowledge sharing and Information Technology (IT) infrastructure on the industrial companies’ innovative capability. The research uses a sample of 90 Brazilian industrial companies and Structural Equation Modeling to verify the hypotheses. The results indicate that companies taking steps to encourage knowledge sharing improve their ability to innovate and this exchange is not limited to the internal environment but advances in interconnection with other companies and partner organizations in the business environment. This initiative opens broad horizons for the development of new skills and capabilities, key factors for promoting greater competitiveness. In addition, the research provides empirical evidence that IT infrastructure favors the integration of knowledge with innovative capability. This result advances the traditional understanding - which considers intellectual capital far superior to infrastructure - and shows that smart integration of knowledge and technology multiplies the company's potential to drive innovation, that is, companies that align IT infrastructure with efforts to share knowledge, innovative ability, a key factor in the pursuit of competitive advantage. This research contributes to the insertion of new insights into the study involving the integration of knowledge, technology and innovation and encourages business managers to increase investments and allocate resources to this integration.